2023
DOI: 10.2147/ijn.s397298
|View full text |Cite
|
Sign up to set email alerts
|

How Effective are Metal Nanotherapeutic Platforms Against Bacterial Infections? A Comprehensive Review of Literature

Abstract: The emergence of multidrug-resistant bacteria has been deemed a global crisis that affects humans worldwide. Novel anti-infection strategies are desperately needed because of the limitations of conventional antibiotics. However, the increasing gap between clinical demand and antimicrobial treatment innovation, as well as the membrane permeability obstacle especially in gram-negative bacteria fearfully restrict the reformation of antibacterial strategy. Metal-organic frameworks (MOFs) have the advantages of adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 144 publications
0
10
0
Order By: Relevance
“…59 In addition, they can increase cytoplasmic levels of reactive oxygen species (ROS), such as hydrogen peroxide, superoxide anions and hydroxyl radicals, by altering the normal function of the respiratory chain in the cell. 60–66 Since the antibacterial effect is due to the release of silver ions from the metal organic framework structure, the different susceptibility of Gram-negative strains ( P. aeruginosa and E. coli ) compared to Gram-positive ones ( S. aureus ) is ascribable to different composition and organization of their cell wall. It has been reported that the different susceptibility of Gram-negative bacteria to silver nanoparticles (AgNPs) could be due to the presence of LPS molecules, which increase the negative charge of the cell membrane compared to Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…59 In addition, they can increase cytoplasmic levels of reactive oxygen species (ROS), such as hydrogen peroxide, superoxide anions and hydroxyl radicals, by altering the normal function of the respiratory chain in the cell. 60–66 Since the antibacterial effect is due to the release of silver ions from the metal organic framework structure, the different susceptibility of Gram-negative strains ( P. aeruginosa and E. coli ) compared to Gram-positive ones ( S. aureus ) is ascribable to different composition and organization of their cell wall. It has been reported that the different susceptibility of Gram-negative bacteria to silver nanoparticles (AgNPs) could be due to the presence of LPS molecules, which increase the negative charge of the cell membrane compared to Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of smart future network computing and intelligent healthcare systems, many possible benefits will reap [ 120 ]. The crucial factor in reaching such capacity is the successful use of healthcare data, which can be a major obstacle since the data is highly heterogeneous and distributed through multiple devices of varying degrees of value and authority to access it [ 121 ]. However, new interventions are being outperformed in several ways due to the present IoT-cloud scenario’s delay, power, and concentrated problems.…”
Section: Open Issue and Future Lines Of Researchmentioning
confidence: 99%
“…21 In addition, a large number of studies have been reported on stimuli-responsive MOFs as a delivery carrier for antibacterial agents under other stimulus conditions such as pH, redox, and adenosine triphosphate (ATP). 22,23 However, it still needs a lot of exploration to construct new MOF-based antibacterial systems with good performance, stability, and long-term antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%